Analisis Power Quality Sistem Kelistrikan Pada Apartemen Malang City Point - Zahra Mulia Sari; Ahmad Hermawan; Sapto Wibowo (Elposys: Jurnal Sistem Kelistrikan, 2020)
The use of equipment with a high non-linear load causes a decrease in the quality of power (Power Quality) at Malang City Point Apartment. Power quality analysis is an important requirement in the electrical system and needs special attention to save energy and costs. Savings can be achieved by reducing or even eliminating losses resulting from the use of non-linear loads. This thesis aims to present the results of an analysis of power quality conditions at Malang City Point Apartments. This analysis includes voltage, current, voltage and current imbalance, power factor, current THD and measured voltage. The system is designed using Web - Based Power Quality Meter (PM 5110) as a measurement tool, then the results are analyzed and compared with existing standards to evaluate power quality in Malang City Point Apartments. Among the various power quality problems measured, it was found that the main problems of power quality in Malang City Point Apartments were the occurrence of overvoltages and current harmonic distortion. So it is necessary to do repairs on this to overcome the overvoltage by reducing the operation of equipment that has a large load and repairing neutral conductors. Furthermore, to reduce the system harmonics, it is designed by designing a single tuned passive filter and simulated using the ETAP software version 16.0.0